2004
DOI: 10.1111/j.1460-9592.2004.01232.x
|View full text |Cite
|
Sign up to set email alerts
|

Diclofenac and metabolite pharmacokinetics in children

Abstract: The formation clearance of the active metabolite 4'-hydroxydiclofenac contributed 19% of total clearance (44.82 l.h(-1) 70 kg(-1)). The rectum is a suitable route for administration of diclofenac in children 2-8 year of age and was associated with a higher relative bioavailabilty than enteric-coated tablets and an earlier maximum concentration (50 vs. 108 min). This pharmacokinetic profile renders diclofenac suppository a suitable formulation for short duration surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…The NSAID diclofenac is commonly prescribed for postoperative analgesia in children, yet its dosing in this patient group remains largely dependent on extrapolation from adult data . Although diclofenac PK in children have been reported , PD for analgesia have not. A pooled data analysis approach was used in this analysis to develop a PD interaction model for diclofenac in combination with acetaminophen for analgesia in children.…”
Section: Discussionmentioning
confidence: 99%
“…The NSAID diclofenac is commonly prescribed for postoperative analgesia in children, yet its dosing in this patient group remains largely dependent on extrapolation from adult data . Although diclofenac PK in children have been reported , PD for analgesia have not. A pooled data analysis approach was used in this analysis to develop a PD interaction model for diclofenac in combination with acetaminophen for analgesia in children.…”
Section: Discussionmentioning
confidence: 99%
“…The rectal route was selected on the basis of available pilot data suggesting that only rectal NSAIDs are effective in preventing post-ERCP pancreatitis, perhaps owing to more rapid and complete bioavailability than with oral administration. 10,18 The indomethacin suppositories were purchased from two vendors: G&W Laboratories and Custom Med Apothecary. Formal potency testing confirmed that the vendors provided indomethacin suppositories that were pharmacodynamically equivalent (Analytic Research Laboratories).…”
Section: Methodsmentioning
confidence: 99%
“…Delayed-release diclofenac (enteric-coated), as used in this study, resists dissolution at the low pH of gastric fluids but is rapidly released in the higher pH environment of the duodenum. It is completely absorbed from the gastrointestinal tract after oral administration, but the bioavailability is only about 50% to 60% because of extensive first-pass metabolism, possibly as a result of intestinal cytochrome P450 (CYP2C9, 3A4, and 3A5) [41]. After the oral ingestion of diclofenac, peak plasma levels are reached in about 2 hours (range, 1 to 4) in fasting healthy volunteers; on the other hand, peak plasma levels with rectal administration are reached within 30 minutes [39].…”
Section: Results Of Pharmacological Approaches To Pepmentioning
confidence: 99%